Experiência de vigilância no setor canavieiro: desafios para interromper a maratona perigosa dos canaviais - Vilela, Rodolfo Andrade de Gouveia; Santos, Simone Alves dos; Silva, Alessandro José Nunes da; Almeida, Ildeberto Muniz de [UNESP] (ABRASCO - Associação Brasileira de Saúde Coletiva, 2014)
The sugar-alcohol sector is growing year by year, especially in the state of Sao Paulo where approximately 42.9% of the sugar-ethanol plants are concentrated. The production chain is a subject for concern to public agencies and to civil society by exposing migrant workers to risks arising from the work process. In Sao Paulo, from 2006-2009, Occupational Health Surveillance (VISAT) set up two initiatives to address problems related to the housing and working conditions of sugarcane workers. The objective of this article presented in the form of an essay is to analyze the experiences in their context. The methodology used combines document analysis with the perception of the authors who participated in the actions. The experience led to improvements in these conditions and fostered public debate on the conditions of such physically demanding work. The interventions resulted in a definition of sanitary norms and initiatives at the legislative and judicial level, but even the most successful measures failed to attain the organizational targets, especially a production remuneration structure that challenges the traditional action of surveillance and the impacts were weakened due to the fragility of worker representation for the sector.

O setor sucroalcooleiro cresce anualmente com participação expressiva do estado de São Paulo que concentra atualmente cerca de 42,9 % das usinas do país. A cadeia produtiva é objeto de preocupação de órgãos públicos e da sociedade civil por expor trabalhadores migrantes a riscos decorrentes do processo de trabalho. Em São Paulo, de 2006-2009, a Vigilância em Saúde do Trabalhador construiu duas iniciativas para enfrentar problemas relacionados às condições de trabalho e moradia de trabalhadores da cana. O objetivo do artigo apresentado na modalidade de ensaio é analisar as experiências em seu contexto. O método usado associa análise documental à percepção dos autores que participaram das ações. As experiências possibilitaram melhorias nessas condições e início de debate público sobre as condições do trabalho exaustivo. As intervenções resultaram na definição de normas sanitárias e iniciativas no nível legislativo e judiciário, mas mesmo aquelas mais exitosas não conseguiram alcançar os determinantes organizacionais, especialmente a remuneração por produção, que desafia a ação tradicional de vigilância e tem seus impactos agravados pela fragilidade da representação dos trabalhadores.
Surveillance experience in the sugarcane sector: challenges in disrupting the perilous marathon of the sugarcane plantations
Keywords: Saúde do trabalhador; Ação intersetorial; Vigilância em saúde; trabalho no cultivo da cana; Occupational health; Inter-sectorial actions; Health surveillance; Work on sugarcane plantations